Adam Smith, the patterns of foreign trade and the division of labour: A country as a Jack-of-all-trades rather than a specialist - Reinhard Schumacher (Duke University, Center for the History of Political Economy (CHOPE), 2016)
Adam Smith is commonly referred to as one of the first who thought of foreign trade in terms of an international division of labour, whereby each country specialises in the production of certain goods. It is argued that he made a strong case for foreign trade on this basis. In this article, I will, in contrast, show that Smith does not understand foreign trade as an international division of labour. Economic progress rather than international trade determines domestic production structures. Apart from domestic development, international trade patterns are affected by transport costs and geographical factors, as well as producer and consumer preferences. In Smith's theory, countries will not specialise, but rather produce similar goods. The division of labour plays a role in Smith's theory of foreign trade, but in a mechanical, not territorial, sense.
Keywords: 330